Customer value creation for the emerging market middle class: perspectives from case studies in India - Sharmelly, Rifat; Klarin, Anton (MDPI AG, 2021)
This paper examines the customer value creation framework and discusses the design of the key elements for product development in emerging markets. A scientometric/bibliometric scoping literature review identifies a clear gap in the current research in studying prerequisites for customer value creation in emerging market contexts. Observing experiences of Daikin and Renault in the context of India, the purpose of this paper is to identify value creation strategic choices following which comprehensive customer value offerings in products and services can be successfully created by firms across the four facets of the framework in emerging markets. Value creation strategies include having a nuanced understanding of the latent contextual needs to offer localized high-quality products that embody distinct functional attributes that provide a functional value and being responsive to specific emotional needs and epistemic experiences of the target customers in product and service offerings to deliver a greater experiential value. Furthermore, the products should adopt a localized operational excellence strategy throughout the value chain to reduce costs for competitive price offerings in order to deliver superior cost value and develop brand image and equity strategy, thereby allowing for the provision of a greater symbolic value. Experiences of successful firms demonstrate the need for extensive local research into the emerging market followed by localization of production and development of a distribution network to be able to offer customized products at competitive prices whilst maintaining the brand value. We thus extend the customer value creation framework by introducing localization as a necessary condition for successful organizational performance in emerging markets.